2017
DOI: 10.1016/j.preteyeres.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast transdifferentiation: The dark force in ocular wound healing and fibrosis

Abstract: Wound healing is one of the most complex biological processes to occur in life. Repair of tissue following injury involves dynamic interactions between multiple cell types, growth factors, inflammatory mediators and components of the extracellular matrix (ECM). Aberrant and uncontrolled wound healing leads to a non-functional mass of fibrotic tissue. In the eye, fibrotic disease disrupts the normally transparent ocular tissues resulting in irreversible loss of vision. A common feature in fibrotic eye disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
249
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(259 citation statements)
references
References 279 publications
(423 reference statements)
5
249
0
5
Order By: Relevance
“…In the process of EMT, epithelial cells can lose tight junction and get mesenchymal markers in EMT process. 47,48 Study reported that CCl 4 (0.1 mL/100 g body weight) induced EMT occurrence by upregulating the contents of α-SMA, vimentin, fibronectin, and Ncadherin, and down-regulating the level of E-cadherin in the rat model of liver fibrosis. 49 Our results showed that the protein level of α-SMA increased and that E-cadherin content declined, which implied that Nano NiO led to EMT occurrence in rat liver.…”
Section: Effects Of Nano Nio On Tgf-β1 Smad and Mapk Pathways Emtmentioning
confidence: 99%
“…In the process of EMT, epithelial cells can lose tight junction and get mesenchymal markers in EMT process. 47,48 Study reported that CCl 4 (0.1 mL/100 g body weight) induced EMT occurrence by upregulating the contents of α-SMA, vimentin, fibronectin, and Ncadherin, and down-regulating the level of E-cadherin in the rat model of liver fibrosis. 49 Our results showed that the protein level of α-SMA increased and that E-cadherin content declined, which implied that Nano NiO led to EMT occurrence in rat liver.…”
Section: Effects Of Nano Nio On Tgf-β1 Smad and Mapk Pathways Emtmentioning
confidence: 99%
“…In view of the complexity and importance of corneal wound healing, a large number of related experiments have been carried out . Despite great progress been made in recent years, there are still limited therapeutic drugs that can promote corneal healing .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that EMT is a vital source of myobroblasts. [30][31][32] Tanjore H. et al 33 found that in lung brosis, approximately 33% of myobroblasts were transformed from epithelial cells through EMT. Therefore, further study on the mechanism of EMT is helpful to understand the pathogenesis of silicosis.…”
Section: Discussionmentioning
confidence: 99%